Applicability of ultrasonography for detection of marginal sinus placenta previa. Issue 1 (8th January 2021) - Ishibashi, Hiroki; Miyamoto, Morikazu; Shinmoto, Hiroshi; Soga, Shigeyoshi; Iwahashi, Hideki; Kakimoto, Soichiro; Matsuura, Hiroko; Sakamoto, Takahiro; Hada, Taira; Suzuki, Rie; Takano, Masashi
Abstract : Abstract: This study aimed to examine whether marginal sinus placenta previa, defined as when the marginal sinus just reaches the internal cervical os and placental parenchyma might be >2 cm from the internal cervical os, can be diagnosed using ultrasonography (US). We identified the placenta previa cases that underwent both US and magnetic resonance imaging (MRI) between April 2010 and December 2018 at our institution. The diagnostic discrepancies for marginal sinus placenta previa between US and MRI were examined retrospectively. Of the 183 cases of placenta previa, 28 (15.3%) cases were diagnosed as marginal sinus placenta previa using MRI. Among them, 18 cases (64.3%) could also be diagnosed using US. The sensitivity and specificity of the diagnosis of marginal sinus placenta previa using US were 64.3% and 92.9%, respectively. A change in US diagnosis occurred in 10 (35.7%) cases, all of which were diagnosed with low-lying placenta previa or marginal placenta previa and did not develop any serious miserable obstetrical outcomes. In conclusion, the diagnostic accuracy of US for detecting marginal sinus placenta previa was not significant. MRI examination may be required to accurately categorize the types of placenta previa.